Development of a Solar System Learning Application Using Markerless Augmented Reality Based on Android - Aditya, Bintang; Al Ikhsan, Safaruddin Hidayat; Wulandari, Berlina (Universitas Bina Sarana Informatika, 2024)
The use of technology in learning has opened up new opportunities to create more interesting and effective learning applications. In learning solar system material, especially at elementary school level, the teaching method still uses books, 2D pictures and teaching aids. However, the limitations of teaching aids which can only be used in class and do not allow them to be taken home can create obstacles in the learning process. To overcome these obstacles, innovation is needed in the development of learning media. One solution that can be used is to apply augmented reality technology. In this research, a solar system object learning application was created that applies markerless augmented reality technology. This application can be used as an alternative to using teaching aids in studying solar system objects. The methodology used in this research is the Multimedia Development Life Cycle (MDLC). The development of this augmented reality application was developed using tools Android Studio by implementing ARCore SDK and Sceneform in implementing markerless augmented reality. The results of this research are in the form of an Android-based learning application that applies markerless augmented reality technology and based on field testing, the effectiveness of the application in delivering solar system materials through the quiz feature is 75%, while 85% of users feel satisfied with the visual and ease of use of the application.